Modern Pesticides and Bobwhite Populations - Kenneth L. Stromborg (National Quail Symposium Proceedings, 2017)
(Invited Paper) Bobwhite (Colinus virginianus) are frequently used as test animals for wildlife tests of pesticides. The organophosphate and carbamate pesticides that have replaced the organochlorines have many desirable properties, but they span a wide range of acute toxicities and some of them affect survival, reproduction, food consumption, behavior, and nervous system enzymes in laboratory tests. Applying these laboratory findings to the field requires assumptions about the severity of exposure in the field. Direct field measurements show that birds may be exposed to significant amounts of these pesticides or even more toxic degradation products under some conditions. Adverse population effects may also result from depression of insect populations during the seasons when bobwhites rely on insects for food.